QUANTITATIVE ASSESSMENT OF TRADITIONAL MEDICINAL PLANTS AND THEIR PHARMACOLOGICAL RELEVANCE IN BARUNEI HILL, ODISHA, INDIA - SNIGDHA BEHERA; SMRUTI RANJAN PANDA; SAMEER JENA; ABANIKANTA BHADRA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study aimed to provide an extensive ethnobotanical survey and quantitative evaluation of medicinal plants to determine the pharmacological utility of the resources, evaluate proximate composition, and mineral content. Methods: The study was completed in 18 months (March 2024–September 2025) in the field with a total of 156 traditional healers and knowledgeable informants, providing an ethnographic examination of their roles in the traditional healthcare of communities and the importance of their relevance to modern healthcare and science products. Quantitative ethnobotanical indices such as use value (UV), fidelity level (FL), relative frequency of citation, and cultural importance index were computed. All 39 recorded species were analyzed using nutritional analysis, comprising proximate composition and mineral analysis. Results: The study recorded 39 species of medicinal plants belonging to 38 genera and 22 families. The UV (UV=0.89) of Azadirachta indica was highest with great application in skin disease, and the highest level of FL (FL=94.7) of Tinospora cordifolia was observed for fever. Andrographis paniculata leaves contained a high level of protein (18.7±1.1 g/100 g). This paper presents a numbers-driven outcome of the research that would be indicative of the therapeutic and nutritional importance of the traditional medicinal plants found within the Barunei Hill. Conclusion: The potential of identified species in the pharmaceutical and nutraceutical industries is significant and a complete clinical assessment is necessary to develop them into a prospective researchable resource.